A PRELIMINARY STUDY OF INVESTIGATING OF COMPOUND GROUP CONTAINED IN ETHANOLIC EXTRACT OF MAHAGONY (Swietenia mahagoni L. Jacq.) SEEDS RELATED TO Α-GLUCOSIDASE INHIBITION - Anjar Purba Asmara (Universitas Syiah Kuala, 2018)
A preliminary study to determine the group of compound contained in the ethanolic extract of mahagony (Swietenia mahagoni L. Jacq.) seeds and its inhibitory activity to a-glucosidase enzyme has been done. The information from this study will be used in the further investigation about the specific constituents related to the bioactivity. The seed was grounded and then extracted with ethanol by maceration technique. The crude extract was separated with liquid-liquid extraction by using n-hexane, ethyl acetate, and methanol as the solvents. The best eluent for isolation, chloroform:ethanol (1:1), was determined by thin layer chromatography while alumina as stationary phase. The isolation step with column chromatography gave two types of isolates, yellow and colorless isolate. In order to get information about the compound, the crude extract was subjected to phytochemical assignment and the isolate with the better activity was analyzed by infrared spectroscopy. The inhibitory activity for the yellow isolate with IC50 as 19.345 ppm was better than the colorless isolate. Therefore, the IR spectroscopy assay was subjected to the yellow isolate. Based on the comparison IR spectra with literatures, it has suggested that the yellow isolate contains tetranortriterpenoid or limonoid group.Keywords: Swietenia mahagoni L. Jacq., diabetes type 2, a-glucosidase, tetranortriterpenoidREFERENCE World Health Organization. Global report on diabetes. http://www.who.int. Accessed on 18 July 2017.Kementerian Kesehatan Republik Indonesia. 2014. Situasi dan analisis diabetes. Jakarta: Pusat Data dan Informasi Kemenkes RI.Dutta, M., Raychaudhuri, U., Chakroborty, R., and Maji, D. 2011. Role of diet and plants on diabetic patients - a critical appraisal. Science and Culture. 77 (3–4).Eid, A.M.M., Elmarzugi, N.A., and El-Enshasy, H.A. 2013. A Review on the phytopharmacological effect of Swietenia macrophylla, Int J Pharm Pharm Sci. 5 (3): 47-53.Bera, T.K., Chatterjee, K., Jana, K., Ali, K.M., De, D., Maiti, M., and Ghosh, D. 2012. Antihyperglycemic and antioxidative effect of hydro-methanolic (2:3) extract of the seed of Swietenia mahagoni (L.) Jacq. in streptozotocin-induced diabetic male albino rat: an approach through pancreas. Genomic Medicine, Biomarkers, and Health Sciences. 4: 107-117.Li, D.D, Chen, J.H, Chen, Q, Li, G.W, Chen, J, and Yue, J.M. 2005. Swietenia mahagony extract shows agonistic activity to PPAR-γ and gives ameliorative effects on diabetic db/db mice. Acta Pharmacol Sinica. 26 (2): 220-222.Sathish, R., Natarajan, K., and Selvakumar, S. 2010. Antidiabetic activity of Swietenia mahagoni seed powder in alloxan induced diabetic mice. Research J. Pharmacology and Pharmacodynamics. 2(4): 296-299.Wresdiyati, T., Sa’diah, S., and Winarto, A., Febriyani, V. 2015. Alpha-glucosidase inhibition and hypoglycemic activities of Sweitenia mahagoni seed extract. HAYATI Journal of Biosciences. 22 (2): 73-78.Sukardiman, Riza, N.F., Rakhmawati, Studiawan, H., Mulja, H.S., and Rahman, A. 2013. Hypoglycemic activity of 96% ethanolic extract of Andrographis paniculata Nees. and Swietenia mahagoni Jacq. combination, E-Journal Planta Husada,. 1.Masitha, M. 2011. Skrining aktivitas penghambatan enzim α-glukosidase dan penapisan fitokimia dari beberapa tanaman obat yang digunakan sebagai antidiabetes di indonesia. Skripsi. FMIPA UI.Aliyan, A.H. 2012. Uji penghambatan aktivitas alfa-glukosidase dan identifikasi golongan senyawa kimia dari fraksi aktif ekstrak biji mahoni (Swietenia macrophylla King). Skripsi. FMIPA UI.Ibrahim, M.A., Koorbanally, N.A., and Islam, M.S. 2014. Antioxidative activity and inhibition of key enzymes linked to type-2 diabetes (a-glucosidase and a-amylase) by Khaya senegalensis. Acta Pharm. 64: 311–324.Harborne, J. B. 1984. Phytochemical methods: a guide to modern techniques of plant analysis. New York: Chapman and Hall.Kadota, S., Marpaung, L., Tohru, K., and Ekimoto, H. 1990. Constituents of the seeds of Switenia mahagoni JACQ. I. isolation, structures, and 1H- and 13C-nuclear magnetic resonance signal assignments of new tetranorterpenoids related to swietenine and swietenolide. Che. Pharm. Bull. 38(3): 639–651.Rahman, A. K. M. S., Chowdhury, A. K. A., Ali, H.A., Raihan, S.Z, Ali, M.S., Nahar, L., and Sarker, S.D. 2009. Antibacterial activity of two limonoids from Swietenia mahagoni against multiple-drug-resistant (MDR) bacterial strains. J Nat Med. 63: 41–45.Yadav, L.D.S. 2005. Organic spectroscopy. Allahabad: Kluwer Academic Publishers.Dewanjee, S., Maiti, A., Das, A.K., Mandal, S.C., and Dey, S.P. 2009. Swietenine: a potential oral hypoglycemic from swietenia macrophylla seed. Fitoterapia. 80: 249–251.Maiti, A., Dewanjee, S., and Sahu, R. 2009. Isolation of hypoglycemic phytoconstituent from Swietenia macrophylla Seeds, Phytother. Res. 23: 1731–1733.Marliana, S.D., Suryanti, V., and Suyono. 2005. Skrining fitokimia dan analisis kromatografi lapis tipis komponen kimia buah labu siam (Sechium edule Jacq. Swartz.) dalam ekstrak etanol, Biofarmasi. 3 (1): 26-31.Nurhayati, Siadi, K., and Harjono. 2012. Pengaruh konsentrasi natrium benzoat dan lama penyimpanan pada kadar fenolat total pasta tomat, Indo. J. Chem. Sci. Vol. 1 (2): 158-163.Siadi, K. 2012. Ekstrak bungkil biji jarak pagar (Jatropha curcas) sebagai biopestisida yang efektif dengan penambahan larutan NaCl. Jurnal MIPA. 35 (1): 80-81.Klein, D.R. 2012. Organic chemistry. New Jersey: John Wiley Sons.Pavia, D.L., Lampman, G.M., and Kriz, G.S. 2001. Introduction to spectroscopy. London: Thomson Learning.Minaeva, V.A., Minaev, B.F., Baryshnikov, G.V., Romeyko, O.M., and Pittelkow, M. 2013. The FTIR spectra of substituted tetraoxa[8]circulenes and their assignments based on DFT calculations, Vibrational Spectroscopy. 65: 147–158.Mootoo, B.S., Ali, A, Motilal, R, Pingal, R, Ramlal, A, Khan, A, Reynolds, W.F, and McLean, S. 1999. Limonoids from Swietenia macrophylla and S. aubrevilleana. J. Nat. Prod. 62: 1514-1517.Lin, B.D., Yuan, T., Zhang, C.R., Dong, L., Zhang, B., Wu, Y., and Yue, J.M. 2009. Structurally diverse limonoids from the fruits of Swietenia mahagoni. J. Nat. Prod. 72: 2084–2090.Cheng, Y.B., Chien, Y.T., Lee, J.C., Tseng, C.K., Wang, H.C., Lo, W., Wu, Y.H., Wang, S.Y., Wu, Y.C., and Chang, F.R. 2014. Limonoids from the seeds of Swietenia macrophylla with inhibitory activity against dengue virus 2. J. Nat. Prod. dx.doi.org/10.1021/np5002829.Zhang, W.M., Liu, J.Q., Deng, Y.Y., Xia, J.J., Zhang, R.N., Li, Z.R., and Qiu, M.H. 2014. Diterpenoids and limonoids from the leaves and twigs of Swietenia mahagoni. Nat. Prod. Bioprospect. 4:53–57.Ma, Y.Q., Jiang, K., Deng, Y., Guo, L., Wan, Y.Q., and Tan, C.H. 2017. Mexicanolide-type limonoids from the seeds of Swietenia macrophylla, Journal of Asian Natural Products Research, DOI: 10.1080/1028-6020.2017.1335715.Zang, Y., amd Xu, H. 2017. Recent progress in the chemistry and biology of limonoids. RSC Adv. 7: 35191–35220.Tan, Q.G., and Luo, X.D. 2011. Meliaceous limonoids: chemistry and biological activities. Chem. Rev., 111, 7437–7522.Fang, X., Di, Y. T, and Hao, X. J. 2011. The advances in the limonoid chemistry of the Meliaceae family. Current Organic Chemistry. 15: 1363-1391.Taylor, D. A. H. The chemistry of the limonoids from meliaceae. https://link.spri-nger.com/book-series/126. Accessed on 21 July 2017.Zang, Y., amd Xu, H. 2017. Recent progress in the chemistry and biology of limonoids. RSC Adv. 7: 35191–35220.